2011
DOI: 10.1089/jwh.2010.2199
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Combination Oral Contraceptives to the Individual Woman

Abstract: Appropriate counseling to raise awareness of the specific characteristics of the different COC options available may optimize adherence and patient acceptability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 98 publications
(102 reference statements)
0
2
1
Order By: Relevance
“…Although literature suggests that mainly the progestin component of HRT increases BC risk (23)(24)(25), a systematic review reported no increased risk after progestin-only OC use (26). Moreover, although synthetic hormone levels in OCs are higher than in HRT (27), we found no increased BC risk for women using OCs as HRT.…”
Section: Discussioncontrasting
confidence: 78%
“…Although literature suggests that mainly the progestin component of HRT increases BC risk (23)(24)(25), a systematic review reported no increased risk after progestin-only OC use (26). Moreover, although synthetic hormone levels in OCs are higher than in HRT (27), we found no increased BC risk for women using OCs as HRT.…”
Section: Discussioncontrasting
confidence: 78%
“…Progestogens can bind to various types of receptors including those for estrogens, androgens, glucocorticoids, and mineralocorticoids, as well as progestogens, and hence, they are involved in a range of different biological activities. 33 Given that some PMS symptoms occur when there is a reduction in the plasma levels of progesterone produced by the corpus luteum, as a consequence of its metabolites pregnenolone and allopregnanolone, it was thought that exogenous progesterone or progestogen might have a beneficial effect on women with PMS. 34 …”
Section: Effect Of Chc Progestogens On Pmsmentioning
confidence: 99%
“…7,8,11,12 Because publicity about venous thromboembolism risks and selective prescribing of specific products 16 are known or suspected to have occurred while the studies were ongoing, serious concern exists that these database deficiencies may have obscured differential misclassification of exposure and outcomes and unequal distribution of confounders between exposure groups. Consequently, undetected biases could have resulted in inflated estimates of venous thromboembolism risk.…”
Section: Background: Data On Venous Thromboembolismmentioning
confidence: 99%